Effectiveness of a Malaysian Media Intervention Workshop: Safe Reporting on Suicide - Lim, Jane Tze Yn; Cheng, Qijin; Ng, Yin Ping; Pheh, Kai Shuen; Panirselvam, Ravivarma Rao; Tay, Kok Wai; Lim, Joanne Bee Yin; Chan, Wen Li; Amer Nordin, Amer Siddiq; Zakaria, Hazli; Bartlett, Sara; Skehan, Jaelea; et al. (Frontiers in Psychology, 2021)
Background: Suicide remains an important cause of premature deaths and draws much media attention. However, unsafe reporting and portrayal of suicides by the media have been associated with increased risk of suicidal behavior. Current evidence suggests that media capacity-building could potentially prevent suicide. However, there are still knowledge gaps in terms of a lack of data on effective strategies for improving awareness and safe reporting of suicide-related media content. This study aims to investigate the effectiveness of a workshop conducted with members of the media community on the safe reporting of suicide-related content. Methods: An interventional single-arm pre and post pilot study was conducted on a sample of the Malaysian media community recruited through purposive and snowball sampling. The media safe reporting workshop was conducted by a suicide prevention expert with a media industry background. Thirty participants completed a self-reported evaluation questionnaire on their awareness and knowledge of reporting on suicide-related media content; before and after the interventional workshop. Results: There was a significant difference between the total scores before and after the intervention, with a large effect size. Post-intervention scores were significantly improved in 8 items, namely those related to the reporting of: (i) the content of any suicide note; (ii) headlines with methods of suicide; (iii) headlines with the location of suicide; (iv) cases of suspected suicide despite the unconfirmed cause of death; (v) suicide news to cater to readers’ interests; (vi) cause of suicide; (vii) details of the location of suicide; and (viii) the negative impact to media community when reporting suicide stories. In particular, there was an improvement in the majority of items for people from the media community with no lived experience of suicidal behavior. Conclusion: The media safe reporting workshop is a potentially effective intervention for improving awareness and knowledge measures relating to safe reporting on suicide among the media community, with a more pronounced effect in those without lived experience of suicidal behavior. Limitations in the sample size, generalizability, short-term evaluation, and lack of a control group warrant future larger, longer-term controlled, and more representative studies.